Antimony-Doped Tin Oxide Hole Injection Interlayer Improving the Efficiency of Perovskite Nanocrystal Light Emitting Diodes - Ioakeimidis, Apostolos; Galatopoulos, Fedros; Athanasiou, M.; Hauser, A.; Rossier, M.; Bodnarchuk, M. I.; Kovalenko, M. V.; Itskos, G.; Choulis, Stelios A. (My University, 2024)
We present significant performance enhancement of CsPbBr3 perovskite nanocrystal (NC) light emitting diodes (PNC LEDs) by incorporation of a solution processed doped metal oxide hole injection interlayer consisting of 10 atom % doped antimony tin oxide (ATO) within the PNC LEDs device architecture. The incorporation of an ATO interlayer between ITO and poly-TPD improves the bottom electrode hole injection properties and provides charge balanced PNC LEDs that show three and half times increased luminance, lower turn-on voltage, and improved maximum current and power efficiency compared to reference CsPbBr3 PNC LEDs incorporating the commonly used PEDOT:PSS hole injection interlayer.
Keywords: Electrodes; Charge balanced; Interfaces; Hole injection layers; Doped metal oxides; Perovskite nanocrystal light emitting diodes